Elaborating Strategies of Sustainable Development at Industrial Enterprises - T. A. Shipilova (Вестник Российского экономического университета имени Г. В. Плеханова)
Elaborating strategy of sustainable development at industrial enterprises is a complicated process aimed at designing and introducing such methods of management, which can provide efficient functioning of the enterprise with regard to ecologic, social and economic aspects. This strategy is a key element of successful running of business in current circumstances, where requirements to sustainability and responsibility to the environment are becoming more and more important. The research found the link between the rate of industry sustainability and provision of sustainable development of enterprises in different industries. The article studies factors that can impact the industrial enterprise in the context of sustainable development and shows the dynamics of correlation between industry sustainability rate and finance results of the enterprise. The author proposed an innovative approach that includes using parameters of generated net accruals in the system of efficiency appraisal, as well as figures of corrected net accruals, where their growth shows the effective transfer to sustainable development.